Do socio-political factors affect investment performance? - Sarwar Uddin Ahmed; Samiul Parvez Ahmed; Mohammad Abdullah; Uttam Karmaker (Cogent Economics & Finance, 2022)
Despite increasing research on the relationship between behavioral factors and investment performance, little is known about the perspective of emerging markets like Bangladesh. This paper investigates the mediating role of socio-political factors in explaining the relationship between behavioral factors and investment performance in the Dhaka Stock Exchange (DSE). Using structural equation modeling (SEM) on 1,123 completed responses, we find that social and political environment mediates investors' behavior in translating into investment performance. The finding suggests behavioral factors and the socio-cultural context of Bangladesh can explain market anomalies seen for decades in the largest stock exchange in the country and demands further research in this direction. Additionally, results show herding effect has the strongest effect on investment performance through combined mediation effect of social and political factors. The study results have significant implications for both theoretical and practical analysts by contributing to the evolution of post-neoclassical finance theories from an emerging market viewpoint and suggesting the probable causes behind historical market instability in DSE, respectively.
Keywords: G40; G41; G10; G11; G14; 330; Social factors; political factors; behavioral factors; investment performance; emerging market; Dhaka Stock Exchange (DSE)